Chronic Venous Disease and In-Hospital Venous Thromboembolism in Critically Ill Patients: A Retrospective Cohort Study of the MIMIC-IV Database - Alperen Kutay Yıldırım; Mesher Ensarioğlu (Journal of Clinical Medicine, 2026)
Background: Chronic venous disease (CVD), and varicose veins in particular, has been reported as a risk factor for venous thromboembolism (VTE) in ambulatory and surgical populations, but its independent contribution to VTE risk in critically ill patients has not been studied. Methods: A retrospective cohort study was performed using the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database, version 3.1. Adult patients with an intensive care unit (ICU) admission and length of stay ≥48 h were eligible. CVD, spanning Clinical-Etiological-Anatomical-Pathophysiological (CEAP) classes C2–C6, was ascertained from ICD-9 and ICD-10 codes using a cross-admission look-back. The primary outcome was in-hospital VTE. Multivariable logistic regression was performed with adjustment for age, sex, severity scores, comorbidities, and ICU treatments; additional analysis was performed with propensity score matching (1:3 nearest-neighbor) and multiple imputation for missing body mass index (BMI). Results: Of 28,741 eligible patients, 544 (1.9%) had documented CVD. Crude VTE incidence was 7.0% in CVD patients vs. 6.2% in those without CVD (unadjusted OR 1.14, 95% CI 0.82–1.59; adjusted OR 1.10, 95% CI 0.77–1.52, p = 0.571). After multiple imputation for BMI, the adjusted association attenuated to 1.03 (0.74–1.45, p = 0.849). Propensity score matching produced consistent results (OR 1.24, 0.84–1.84). In an exploratory severity analysis, crude VTE rates were 6.2% without CVD, 6.4% with uncomplicated CVD, and 16.7% with complicated CVD; the complicated stratum comprised only 30 patients with 5 events (aOR 2.90, 95% CI 1.09–7.08, p = 0.032), and the test for trend was not significant (p = 0.31). CVD patients received less pharmacological prophylaxis than non-CVD patients (61.2% vs. 66.0%, p = 0.023). Conclusions: Chronic venous disease was not independently associated with in-hospital VTE in this critically ill cohort, and the modest crude association attenuated further after accounting for BMI. An exploratory analysis suggested a higher risk in complicated CVD, but the stratum was too small and the trend test too weak to support a severity gradient; this requires confirmation in cohorts with prospective CEAP classification. CVD patients received less thromboprophylaxis than patients without CVD (61.2% vs. 66.0%, p = 0.023), although this difference did not persist after adjustment (aOR 0.88, 95% CI 0.74–1.06, p = 0.172).